Doctor patient relationship as human link transcendental in health organizations (Revista Venezolana de Salud Pública, 2018)
The doctor-patient relationship a vital human bond is contextualized towards meeting the conscious or unconscious patient demands. It is an interaction that influences the patient's perception about the quality of care and their willingness to return to a following query, facilitating consensus decision-making, leaving the ultimate satisfaction of both parties for the service provided / received.
Keywords: medical interview; health care organization; quality; patient-physician relationship